Cognitive perspectives on Israelite identity - Nestor, Dermot (Library of Hebrew bible/Old Testament studies, 2010)
Introduction -- The rise of the concept of race -- Social evolution and race -- Human evolution and the concept of culture(s) -- Archaeology and evolution -- Archaeology and the question of national identity : Gustav Kossinna -- Archaeology and culture : v. Gordon Childe -- Archaeology and the identity of Israel -- The emergence of ethnicity -- Primordialism and instrumentalism in the study of ethnicity -- Cognitive perspectives on ethnicity and identity -- Ethnicity as cognition : Pierre Bourdieu -- The loss of innocence -- New archaeology and the ethnic interpretation of style -- Style as active comunication -- The archaeology of practice -- Biblical archaeology and la longue durée -- Archaeology and Israelite identity -- Israel in the Merneptah Stele -- Israel as an essentialist category of social cognition -- Israelite ethnicity and biblical archaeology -- Ethnic sentiments in the Hebrew Bible -- The Hebrew Bible and the creation of Israelite identity -- Ideology, doxa, and the boundaries of Israelite identity -- Common sense as social power